O surgimento do institucionalismo Norte-Americano: ensaio sobre o pensamento e o tempo de Thorstein Veblen - Marco Antonio Ribas Cavalieri (2009)
Similarly to the great names of political economy, Thorstein Veblens writings have been animating a myriad of economic studies for more than a century. This way, within what seems to be an eternal re-founding of a veblenian paradigm it is straightforward to perceive a clear trend: the abandon of the attitude of positing Veblen in his times, of analyzing him as a man from the Gilded Age and the Progressive Era. Therefore, this Thesis intends to recover a theme that the earlier studies concerning Thorstein Veblen had presented. That theme was to evaluate his work within the rich scenario when his native nation had come to be the worlds capitalism leader. Hence, for that objective this work takes the Sociology of Scientific Knowledge of the Scottish Strong Programme, founded by the pioneer David Bloors book Knowledge and Social Imagery, as an auxiliary. The central hypothesis is that the Veblens institutional economics structurally reflects the American nineteenth century pathway. Meanwhile, it is remarked that his system embraces recurrent ideas sustained by north-American anticonservatives since the colonial times.